The state of access : success and failure of democracies to create equal opportunities - Jong, Jorrit de.; Rizvi, Gowher (Cambridge, MA : Ash Institute for Democratic Governance and Innovation, John F. Kennedy School of Government, Harvard University ; Washington, D.C. : Brookings Institution Press, 2008)
"A comparative, cross-disciplinary exploration of the ways in which democratic institutions fail or succeed to create the equal opportunities that they have promised to deliver to the people they serve"--Provided by publisher.
Access and the state -- The castle and the village: the many faces of limited access / Jorrit de Jong and Gowher Rizvi -- Access to political decisionmaking -- Toward participatory inclusion: a gender analysis of community forestry in South Asia / Bina Agarwal -- Access to government in Eastern Europe: environmental policymaking in Hungary / Susan Rose-Ackerman -- Access to the economy -- Economic entitlements: facilitating immigrant entrepreneurship / Jorrit de Jong and Peter Kasbergen -- Appropriate fit: service delivery beyond bureaucracy / Guy Stuart -- Access to public services -- Revenues and access to public benefits / Michael Lipsky -- Bureaucratic bias and access to public services: the fight against non-take-up / Arre Zuurmond -- Providing services to the marginalized: anatomy of an access paradox / Albert Jan Kruiter and Jorrit de Jong -- Access to accountable government -- Calling 311: citizen relationship management in Miami-Dade County / Alexander Schellong -- Demanding to be served: holding governments to account for improved access / Anwar Shah -- Access to justice -- Access to justice in the United States: narrowing the gap between principle and practice / Deborah L. Rhode -- Legal empowerment of the poor: innovating access to justice / Maaike de Langen and Maurits Barendrecht -- The access agenda -- The dynamics of access: understanding "the mismatch" / Jorrit de Jong and Gowher Rizvi.
Includes bibliographical references and index.
Donated By Akbar Ali Khan
Keywords: Equality; Democracy; Economic history; Social justice; Social sciences